Institutional ownership and dividend decisions in Bangladeshi enterprises: A moderating role of profitability - Hosain, Md. Zakir; Uddin, Md Parvez (Asian Economic and Financial Review, 2025)
This study explores the relationship between institutional ownership and dividend decisions in Bangladeshi enterprises, as well as the moderating impact of profitability on this association. The study uses a sample of 85 Bangladeshi companies, encompassing 1,176 firm-year observations from 2008 to 2023. Panel data are analyzed using descriptive statistics, pairwise correlation, diagnostic tests, and the Tobit model. The Bootstrap standard error estimation technique is applied to enhance model efficiency. The results suggest that profitability significantly strengthens the impact of institutional ownership on dividend payments. Specifically, firms with higher profitability tend to increase dividends when they have substantial institutional shareholding, as institutional investors favor firms that provide stable returns, particularly when the firms demonstrate strong financial health. The findings provide financial managers, portfolio managers, and investors with valuable insights into the association between institutional shareholding and dividend distribution, as well as the effect of profitability on this relationship. Managers can formulate dividend policies aligned with institutional investors’ preferences. The findings also enable investors to purchase shares of companies whose dividend policies match their personal preferences. Portfolio managers can use these insights to select the best securities for their clients.